Institutional reforms to strengthen patient and public involvement in the Czech Republic since 2014 - Dobiášová, Karolína; Kotherová, Zuzana; Numerato, Dino (Health policy (Amsterdam, Netherlands), 2021)
Many countries aim to strengthen patient and public involvement (PPI) in healthcare decision-making. This article discusses the institutionalisation of PPI in the Czech Republic from 2014 to the present based on a review of available documents as well as interviews with policymakers and representatives of patients' organisations. Important steps that contributed to the institutionalisation of PPI were the establishment of the Ministry of Health's (MoH) Patients' Council and the MoH's Patients' Rights Support Department. The institutionalisation of PPI was facilitated through the bottom-up engagement of patients, top-down policy developments, transnational pressures, the support of statutory insurance funds and the pharmaceutical industry, and macro-societal developments. Compared to other post-socialist countries, the institutionalisation of patient involvement in policymaking is amongst the most developed. Although the pharmaceutical industry enhanced PPI, its involvement raised ethical concerns. Various stakeholders called for public funding of patients' organisations to provide them with a stable income and more independence. In summary, the role of patients has been strengthened through macro-institutional involvement. Further progress will demonstrate whether these changes at the macro level of policymaking will stimulate more profound transformations at the meso and micro levels and, therefore, contribute to more profound cultural changes in doctor-patient relationships.
Keywords: Czech republic; Česká republika; lidé; Health policy development; zapojení pacienta; Patient Participation; Czech Republic; Patient and public involvement; vytváření politiky; Policy Making; Health system reform; Humans